The Effect of Klotho Treatment on Atherogenesis, Blood Pressure, and Metabolic Parameters in Experimental Rodent Models - Kamari, Y.; Fingrut, O.; Shaish, A.; Almog, T.; Kandel-Kfir, M.; Harats, D.; Rubinek, T.; Wolf, I. (Hormone and Metabolic Research, 2016)
Klotho is a transmembrane protein, expressed mainly in the kidneys and the choroid plexus. The extracellular domain of klotho is composed of 2 internal repeats, KL1 and KL2, which can be cleaved and act as hormones. Klotho-deficient mice develop a phenotype resembling human aging. Laboratory and clinical data suggest a favorable effect of klotho on atherosclerosis, high blood pressure, and metabolic syndrome. Therefore, we aimed to study the effect of klotho treatment on atherogenesis, blood pressure, and metabolic parameters in experimental rodent models. Fructose-fed Sprague-Dawley rats (metabolic syndrome model) and apolipoprotein E (apoE -/-) knock-out mice (atherosclerosis model) were treated with either klotho or its active domain KL1. In apoE –/– mice, klotho unexpectedly elevated plasma cholesterol and triglyceride levels compared to the control group. Yet, it did not increase the aortic sinus atherosclerotic lesion area. In fructose-fed Sprague-Dawley rats, klotho treatment did not lower blood pressure or plasma triglyceride levels. Although KL1 treatment did not lower blood pressure or plasma insulin levels, it significantly reduced the elevation of total plasma triglyceride levels (from 2.3-fold to 1.6-fold, p<0.05) due to lower triglyceride-rich VLDL levels. Klotho did not show any beneficial effects on atherosclerosis and components of the metabolic syndrome and was associated with increased plasma cholesterol levels. On the other hand, treatment with KL1 may lower plasma triglyceride levels independent of insulin. Additional studies are required in order to decipher the complex role of klotho and its active domains in the regulation of plasma lipid levels.
Keywords: klotho; cholesterol; triglycerides; hypertension; metabolic syndrome; atherosclerosis